Univalence criteria of certain integral operator - Eghbiq, Abdussalam; Maslina Darus, (Pusat Pengajian Sains Matematik, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
In this paper, univalence criteria of certain integral operator defined by a generalised derivative operator is obtained.